2011
DOI: 10.1175/2010jcli3627.1
|View full text |Cite
|
Sign up to set email alerts
|

Peaks-over-Threshold Study of Trends in Extreme Rainfall over the Iberian Peninsula

Abstract: A peaks-over-threshold (POT) approach is used to study trends in extreme rainfall over the Iberian Peninsula (IP) at a daily scale. Records from 52 observatories regularly distributed over Iberia with no missing data were available for the common period from 1958 to 2004. The POT approach was used because it is particularly effective at extracting information concerning true extreme events. A generalized Pareto distribution fit was made to the data involving time-dependent parameters to account for possible te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 39 publications
3
60
0
3
Order By: Relevance
“…They pointed to an important consequence: autumn, instead of winter, would be the season with most extreme rainfall in the western IP due to the sharp increase in the RLs in the future. This is coherent with previous results [9,10] indicating a significant positive trend for extreme rainfall over the western half of the IP and with the findings of a regional study [12] of an area in the southwestern IP, which showed the same behavior. An increase in the frequency of extreme precipitation in autumn for the same area of the IP has been described as being due to increased northwesterly flows [25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…They pointed to an important consequence: autumn, instead of winter, would be the season with most extreme rainfall in the western IP due to the sharp increase in the RLs in the future. This is coherent with previous results [9,10] indicating a significant positive trend for extreme rainfall over the western half of the IP and with the findings of a regional study [12] of an area in the southwestern IP, which showed the same behavior. An increase in the frequency of extreme precipitation in autumn for the same area of the IP has been described as being due to increased northwesterly flows [25].…”
Section: Discussionsupporting
confidence: 93%
“…Some studies of extreme rainfall trends for the IP have used the statistical extreme value theory (EVT) and some the block maxima (BM) [9] or the peaks-over-threshold (POT) approaches [10,11]. These methods each have advantages and disadvantages, and it is important to compare the results they give.…”
Section: Introductionmentioning
confidence: 99%
“…A sensitivity analysis was performed by estimating four different GPD models. Acero et al (2011) use the POT-GDP approach where thresholds are made time-varying, allowing them to change linearly over time. An automatic declustering approach was used to select independent extreme events exceeding the threshold.…”
Section: Assuming a Non-stationary Climatementioning
confidence: 99%
“…The POT approach ensures that other extreme rainfall events apart from the annual maxima are included [3,4], but suffers from the subjective selection of a suitable threshold [5,6] and potential correlation between extreme events [7]. In contrast, the AM approach is simple, hence remaining popular in extreme rainfall studies [7].…”
Section: Literature Reviewmentioning
confidence: 99%